The metabolic syndrome: artifice or reality? - Garmendia Lorena, Fausto (2020)
The validity of the metabolic syndrome (MS) to predict the cardiovascular risk (CVR). Peruvian and international scientific literature was reviewed about the original proposal of syndrome X and main guidelines of MS, agreed by different organizations and medical-scientific institutions. The great diversity of criteria used by the guidelines was highlighted, which, in comparing the prevalence of MS, demonstrated a wide and significant diversity of results. The evaluation of the predictive power of the development of cardiovascular events of guidelines and their singular components showed that the independent components of RCV have equal or greater power than the whole MS. It is concluded that it is unnecessary to use the proposed guidelines of the MS to establish the CVR, since each of its components is an independent factor of cardiovascular risk, including prediction of cardiovascular events in longitudinal studies.